Deflection hardening behaviour of jute strands reinforced lightweight cementitious composite - Sadiq, K.; Bzeni, D.; Shaikh, Faiz (ELSEVIER SCI LTD, 2015)
This paper presents deflection hardening behaviour of jute strands reinforced lightweight cementitious composite under flexural loading. The effects of volume fractions of jute strands and the amount of lightweight fine aggregate (LWFA) as partial replacement of natural fine aggregate (NFA) on the deflection hardening and multiple cracking behaviour are also evaluated in this study. Five different types of mortars containing 0%, 50%, 75%, 100% and 150% (by wt.) light weight fine aggregates are produced. Jute strands reinforced cement composites containing four different volume fractions of jute strands of 2%, 4%, 6% and 8% are prepared using each type of light weight mortar. The specimens were tested in third-point loading and the results show deflection hardening with multiple cracking of jute strand reinforced lightweight cement composites. The composites also show high toughness and toughness indices values, indicating the potential of this environmental friendly highly ductile composite in building and construction applications.